2003
DOI: 10.1097/00130832-200306000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Update on wheat hypersensitivity

Abstract: Diagnostic skin prick and in-vitro tests measuring sensitization against water/salt-soluble wheat proteins have poor predictive values. Quantification of gliadin-specific IgE in serum or skin prick testing with gliadin could serve as an additional tool in the diagnostic work-up of allergy to ingested wheat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
2
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 45 publications
1
79
2
3
Order By: Relevance
“…However, in patients with classical wheat allergy, the allergens responsible for symptoms have not been defined because serum IgE reacted to both water/saltsoluble and -insoluble proteins (32-36). As just described, it is considered that causative allergens are variable among the clinical forms (37,38). Recent studies have shown that -5 gliadin is a good candidate as a diagnostic tool for not only WDEIA but also immediate allergy to wheat (39 -41).…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients with classical wheat allergy, the allergens responsible for symptoms have not been defined because serum IgE reacted to both water/saltsoluble and -insoluble proteins (32-36). As just described, it is considered that causative allergens are variable among the clinical forms (37,38). Recent studies have shown that -5 gliadin is a good candidate as a diagnostic tool for not only WDEIA but also immediate allergy to wheat (39 -41).…”
Section: Discussionmentioning
confidence: 99%
“…The main symptom of food allergy to wheat in children is atopic eczema/ dermatitis syndrome (AEDS), 7,8) whereas in adults, the most frequent and severe symptom is wheat-dependent exercise-induced anaphylaxis (WDEIA). 7,9,10) Gliadins and glutenins, the major proteins of wheat flour, are involved in the development of food allergy to wheat.…”
Section: Improvement Of Digestibility Reduction In Allergenicity Anmentioning
confidence: 99%
“…10,11 . Food allergy is generally caused by a cross-linking of allergens and human immunoglobulin E (IgE), and degranulation of mast cells 2,6 .…”
Section: Introductionmentioning
confidence: 99%
“…IgE recognizes linear 5~10 amino acid sequences of allergen proteins, which are termed epitopes. Among many wheat allergen proteins, gliadins and glutenins have been well studied [10][11][12] . Tanabe et al identified a glutenin epitope (QQQPP) 15 and gliadin epitopes (PQQPF and QQPFP) 16 for atopic dermatitis.…”
Section: Introductionmentioning
confidence: 99%